Professional Apache Tomcat 5 - Chopra, Vivek (Wiley Pub., 2004)
Chapter 3: Tomcat Installation; Installing the Java Virtual Machine; Installing Tomcat; The Tomcat Installation Directory; Troubleshooting and Tips; Summary; Chapter 4: Tomcat Architecture; An Overview of Tomcat Architecture; Summary; Chapter 5: Basic Tomcat Configuration; Tomcat 5 Configuration Essentials; Tomcat 5 Web-Based Configurator; Files in CATALINA_ HOME/conf; Basic Server Configuration; Summary; Chapter 6: Web Application Configuration; The Contents of a Web Application; The Deployment Descriptor (web. xml); Summary; Chapter 7: Web Application Administration.